Magnolia table : a collection of recipes for gathering - Gaines, Joanna, 1978-; Stets, Marah (William Morrow, an imprint of HarperCollinsPublishers, 2018)
Collects more than one hundred classic recipes for meals, snacks, desserts, and small plates, including chicken pot pie, asparagus and fontina quiche, overnight French toast, and fried chicken with sticky poppy seed jam.